2017
DOI: 10.15446/caldasia.v39n2.63489
|View full text |Cite
|
Sign up to set email alerts
|

Variación espacial y temporal de la herpetofauna en ecosistemas de sabanas inundables de la Orinoquía-Colombia

Abstract: EcologíaVariación espacial y temporal de la herpetofauna en ecosistemas de sabanas inundables de la Orinoquía-Colombia RESUMENSe comparó la diversidad de anfibios y reptiles en bosques de vega, de galería y sabanas y entre las épocas seca y de lluvias en ecosistemas de sabanas inundables. Se realizó un muestreo en tres sitios en cada época climática, mediante los métodos de encuentro visual y trampas de caída con barreras de interceptación. El esfuerzo de muestreo para cada cobertura fue de 252 horas de recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…This climatic condition has acted as a strong selective pressure to the anuran ensembles that inhabit the flooded savannas. It has caused great changes of its richness, composition, and abundance between dry and wet seasons (Montoya et al, 2011;Angarita-Sierra, 2014;Blanco-Torres, 2017). For example, three out of five frog families present in this ecosystem (Leptodactylidae, Bufonidae and Microhylidae) contain the highest species abundance and are composed by species with opportunistic life traits, semi-fossorial habits, low water dependence, and wide habitat preference such as Leptodactylus fuscus (Schneider, 1799), Leptodactylus fragilis (Brocchi, 1877), Rhinella beebei (Gallardo, 1965;Dixon & Staton, 1976;Duellman & Trueb, 1994;Tárano, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This climatic condition has acted as a strong selective pressure to the anuran ensembles that inhabit the flooded savannas. It has caused great changes of its richness, composition, and abundance between dry and wet seasons (Montoya et al, 2011;Angarita-Sierra, 2014;Blanco-Torres, 2017). For example, three out of five frog families present in this ecosystem (Leptodactylidae, Bufonidae and Microhylidae) contain the highest species abundance and are composed by species with opportunistic life traits, semi-fossorial habits, low water dependence, and wide habitat preference such as Leptodactylus fuscus (Schneider, 1799), Leptodactylus fragilis (Brocchi, 1877), Rhinella beebei (Gallardo, 1965;Dixon & Staton, 1976;Duellman & Trueb, 1994;Tárano, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The main assumption that supports the IBIA is the closed ecological relationship between the anuran assemblage and the natural vegetation of the flooded savannas (Angarita-Sierra, 2014, Pedroza-Banda et al, 2014, Blanco-Torres et al, 2017. The IBIA has been developed in a similar way as Shulse et al (2009) and Waringer et al (2005) as follows.…”
Section: Development Of the Index Of Biotic Integrity Based On Anurans (Ibia)mentioning
confidence: 99%
See 2 more Smart Citations
“…In our study area (in the department of Casanare) 46 species of anurans have been reported, of which 28 breeds in lentic bodies of water (Pedroza-Banda et al, 2014). Also, the natural savannas have the greatest abundance and richness of anurans in the region (Blanco-Torres et al, 2017), but they are highly transformed by land-use changes for cattle ranching (Etter et al, 2008;Angarita-Sierra, 2014;Angarita-Sierra, 2021). We evaluated larval stage anuran assemblages inhabiting different bodies of water with the following objectives: 1) to determine the variation in species diversity between natural ponds (immersed in savannas or gallery forest) and anthropogenic puddles (immersed on roads or pastures); 2) to characterize temporal changes in environmental variables between bodies of water shaped by aquatic physicochemical variables, vegetation structure, land use management practices, and distance to landscape elements; and 3) to determine the relationship between changes in species diversity and the environmental variables.…”
Section: Introductionmentioning
confidence: 95%